2015
DOI: 10.1186/s13002-015-0007-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of ichthyofauna by artisanal fishermen at two protected areas along the coast of Northeast Brazil

Abstract: BackgroundFishing is one of the oldest human activities and constitutes a source of income and livelihood for millions of people, particularly in coastal regions. This study aimed to characterize the types of fish use and test whether there is a relationship between uses of fish in the communities studied.MethodsThis study was conducted during the months of January to October 2013, on the beaches of Tamandaré and Batoque, both located in Northeast Brazil. Information was collected through interviews with 75 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
2
11
0
1
Order By: Relevance
“…Such knowledge is increasingly being applied to the study of climate change through ethno-climatological approaches [20–22], which can be utilized to determine the potential consequences of climate change on exploited populations across different spatial and temporal scales. Information from such studies can be used for participative management [2325] and to guide future research [26]. Moreover, the integration of scientific and traditional knowledge facilitates and supports social negotiation during the development and implementation of resource management measures [15, 2729].…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge is increasingly being applied to the study of climate change through ethno-climatological approaches [20–22], which can be utilized to determine the potential consequences of climate change on exploited populations across different spatial and temporal scales. Information from such studies can be used for participative management [2325] and to guide future research [26]. Moreover, the integration of scientific and traditional knowledge facilitates and supports social negotiation during the development and implementation of resource management measures [15, 2729].…”
Section: Introductionmentioning
confidence: 99%
“…However, local fishers recognize that fishing period can change due to environmental variations that influence the life cycle (reproduction period) and ontogenetic cycle (differences in habitat between juveniles and adults) of some target species. Previous studies have also found an association between fishing period and greater precipitation or drought period in many communities along the Brazilian coast (e.g., southeastern Brazil: Begossi 1996and Silvano et al 2010, northeastern Brazil: Costa-Neto 2001and Pinto et al 2015.…”
Section: Macrodon Ancylodonmentioning
confidence: 89%
“…The LEK of artisanal fishers provides knowledge about ecological, taxonomic, and ethological aspects of aquatic communities that are important for inventories, especially in places where scientific studies are scarce (Mourão & Montenegro 2006, Silvano & Begossi 2012, Pinto et al 2015, Pitcher & Lam 2015. Analyzing the interactions between fishers and fishery resources is important to understand distinct forms of use, capture, categorization, and commercialization of target species (Begossi 2006, Souza et al 2007, Gerhardinger et al 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Batrachoides surinamensis is reported in literature as ranging in Brazil from Amapá to Bahia states and it was recently recorded in Amapá (Maia et al 2016), Pará (Ferreira et al 2011), Maranhão (Piorski & Nunes 2010), Piauí (Mai et al 2012), Ceará (Osório et al 2011), Paraíba (Oliveira 2011), Pernambuco (Pinto et al 2015), and Alagoas (Paiva et al 2013). In the conservation status may not represent historical declines.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%